Meritocracy, the Reproduction of Inequality, and the Academic Scandal in Indonesia: Philosophical Perspective of Michael Sandel - Tan, Peter; Kosat, Oktovianus (Indonesian Journal of Educational Research and Review, 2024)
The practice of academic cheating is one of the biggest scandals in the educational process at various universities throughout Indonesia. This study aims to elaborate on the issue from Michael Sandel's philosophical criticism of the tyranny of meritocracy and the reproduction ofeducational inequality. The research uses the literature review research method, which is carried out by identifying, analyzing, and interpreting Sandel's works critically, especially his book, The Tyranny of Merit: What Becomes the Common Good? The results of this study indicate that academic cheating in university is not only the result of personal academic incompetence or degradation of personal moral integrity but mainly the result of the educational system and paradigm that exalts and adores meritocracy. Under the tyranny of meritocracy, the academicians concentrate on pursuing academic titles and individual pride rather than being an organic and humanistic intellectual. It can be concluded that under meritocracy, the education system fails to implement its humanistic and liberating role and instead reproduces the new social inequality and oppression. This research has implications for the revitalization of education’s role as an agent of liberation, equality, and justice in Indonesia.